PLANNING AND EXPERIMENTAL STUDIES OF SELECTION THE OPTIMAL WELDING MODE BY THE FRICTION OF FITTING RODS - Buzauova, Toty; Turekhanov , Bayanbek; Mateshov , Arman; Zhauyt, Algazy; Ismagulova, Sarakul; Zhunisbekov, Seitbek (Journal of Applied Engineering Science, 2022)
The methods of friction welding of various materials have been studied, as well as the design and capabilities of the device for friction welding have been determined. The design of the device for friction welding on the basis of a lathe has been developed taking into account the established requirements and recommendations of machine-building enterprises. To study the influence of technological factors on the quality of welded joint formation, a full factorial experiment (FFE) of type 22 was set up according to the plan. The adequacy of the planned experiment was confirmed by calculations (Fcalcul. = 1.1 <Ftabl. = 4.46.) on the basis of which a full-scale experiment was carried out. According to the results of the experimental plan, it was found that the heating time of the workpieces being welded has the most significant effect on the total length of the seam upsetting. The optimal mode with the correct formation of the burr has been chosen. The convergence of the full-scale test results with the planning of the Type 22 full factor experiment has been identified, resulting in the determination of the optimal mode.